Efficacy of cultural control for date palm borer management - Latifian, Masoud; Rad, Bahar (Indian Journal of Plant Protection, 2020)
The effects of cultural controls on the major date palm borer pests, including Oryctes elegans, Pseudophilus testaceus and Microcerotermes diversus were studied by applying cluster-sampling method. Macheak method was used for estimating pest infestation and key pathology of date palm borer pest injury was used for distinguishing their injuries. Cultural management factors included in the study were tillage, fertilization, irrigation, pruning, bunch covering and bunch arrangement. Data were analyzed by multiple regressions. Results showed that tillage, leaf pruning, petiole pruning and sucker removal had suitable effects in decreasing the date palm borer pest infestations. The cumulative effects of cultural factors were calculated. Results showed that petiole pruning, tillage, leaf pruning and sucker removal had the highest rate of control,respectively. Petiole pruning is the most effective factor in reducing the severity of injuries caused by the borer pests, viz., termites, horned beetle and long antennae beetle. Tillage practices and leaf pruning had the greatest effect in reducing termite, long antennae and horned beetles, respectively. Sucker removal operations had the greatest effect in reducing the severity of injuries of horned and long antennae beetles in date palm trees.